Anti-SARS-CoV-2 IgG antibodies induced by the BNT162b2 mRNA vaccine is age-dependent and influenced by a previous natural SARS-CoV-2 infection - Pratò, Simone; Paladino, Maria Emilia; Riva, Michele Augusto; Cavallero, Annalisa; Latocca, Raffaele; Biondi, Andrea; Bonfanti, Paolo; Belingheri, Michael (Acta Biomedica Atenei Parmensis, 2022)
Background and aim: our study aimed to investigate the association between anti-SARS-CoV-2 IgG level after two doses of BNT162b2 vaccine and the previously infected/infection-naïve status, age, and gender in a population of health care workers (HCWs).Methods: all the population of immunocompetent HCWs were vaccinated with two doses of BNT162b2 based on a technical data sheet. SARS-CoV-2 IgG assay was performed 25 to 32 days after the second dose. Anti-SARS-CoV-2 IgG level was used as a categorical variable, since 2080 BAU/ml was the median IgG value. The multivariate logistic regression model included the previously infected/infection-naïve status, age groups, and gender.Results: All HCWs tested were seropositive. The odds ratio (OR) for anti-SARS-CoV-2 IgG> 2080 BAU / ml between previously infected and infection-naïve HCWs was 2.05 [95% CI 1.1-3.8].  Older age groups had lower percentage of HCWs with anti-SARS-CoV-2 IgG> 2080 BAU / mL than younger groups. Finally, no association between gender and IgG level was found.Conclusions:our study showed an excellent antibody response to vaccination with BNT162b2 after two doses. A significant difference was observed between anti-SARS-CoV-2 IgG level with age and previous SARS-CoV-2 infection status.